ChemInform Abstract: Intramolecular [3 + 2]‐Cycloadditions of Azomethine Ylides Derived from Secondary Amines via Redox‐Neutral C—H Functionalization. Issue 18 (May 2015) - Mantelingu, Kempegowda; Lin, Yingfu; Seidel, Daniel
Abstract A vast number of secondary amines such as tetrahydroquinoline, tryptoline, pyrrolidine, azepane, morpholine, dihydroindole, and dihydropyrrole derivatives are condensed with azomethine ylides deriving from aldehydes bearing a pendant dipolarophile.